Legal Review of the Role of the Ministry of Finance in Filing Bankruptcy Applications Against State-Owned Bankruptcy Debtors - Dios Ferdian Harefa; Muhammad Afif Mahfud (Faculty of Law, Universitas Pekalongan, 2022)
The purpose of this research is to find out how the Bankruptcy Regulations Against BUMN and how the Role of the Minister of Finance in Submitting the Application for a Statement of Bankruptcy Against BUMN Debtors, which with normative legal research methods are concluded: 1. Arrangements for bankruptcy of a State-Owned Enterprise (BUMN) are regulated as a whole in Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations. More specifically, the regulation is regulated in Article 2 paragraph (5) of Law Number 37 of 2004. Bankruptcy arrangements for BUMN have ambiguity or multiple interpretations related to the explanation of Article 2 paragraph (5) regarding BUMN that are engaged in the public interest, the Bankruptcy Law does not provide restrictions the criteria for the public interest are strictly defined, only using limits on the size and origin of the capital but not clearly explaining that what is meant by public interest is BUMN Perum. The existence of disharmony of the law regarding the authority of the Minister of Finance in insolvency of BUMN Perum must also pay attention to the principle of Lex posteriori derogate legi priori, namely the new regulation defeats or paralyzes the old regulation. 2. The Minister of Finance has an important role in submitting an application for a declaration of bankruptcy against a State-Owned Enterprise (BUMN). The Minister of Finance has a role to bankrupt a BUMN that is engaged in the public interest (perum) for the benefit of the country's economy, or to be one way to save the country's economy through bankruptcy. The role of the Minister of Finance in the bankruptcy of SOEs in accordance with Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations is as an applicant for a declaration of bankruptcy against State-Owned Enterprises (BUMN) engaged in the public interest or Perum. In the event that BUMN creditors who will file for bankruptcy must first submit an application to the Minister of Finance through the Legal Bureau for State Property Law, Company, and Legal Information which will then be submitted to the Minister of Finance to immediately submit a request for a declaration of bankruptcy against BUMN to the Chairperson of the Court.Kata kunci: bangkrut; Menteri Keuangan;